Electrolyte slurry and preparation method thereof, solid electrolyte film and diaphragm-free all-solid-state battery

By using a blended modified electrolyte slurry, combined with polysulfur compounds, inorganic materials, second polymers and lithium salts, the problem of insufficient electrochemical performance and high temperature stability of solid-state batteries is solved, and higher electrochemical performance and better high temperature stability are achieved.

CN119920952APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD

Patent Information

Application Number
CN202411494981.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There is still room for improvement in the electrochemical performance and high temperature stability of existing solid-state batteries.

Method used

By using an electrolyte slurry made from blended modification of polysulfide compounds, inorganic materials, second polymers and lithium salts, the polysulfide compounds have higher ionic conductivity and thermal stability, which can improve the electrochemical performance and high temperature stability of solid-state batteries.

Benefits of technology

This technical method significantly improves the electrochemical performance and high temperature stability of solid-state batteries, and enhances the cycle stability and safety of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_24
    Figure SMS_24
  • Figure SMS_25
    Figure SMS_25
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to electrolyte slurry and a preparation method thereof, a solid-state electrolyte film and a diaphragm-free all-solid-state battery. The electrolyte slurry is mainly prepared by blending and modifying a first polymer, an inorganic solid electrolyte, inorganic ceramic, a second polymer and a lithium salt; the first polymer is a polysulfide compound, and the polysulfide compound comprises one or more of a monosulfide polymer, a disulfide polymer and a polysulfide polymer. The polysulfide is introduced into a raw material system, so that the electrochemical performance and the high-temperature stability of the solid-state battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to an electrolyte slurry and a preparation method thereof, a solid-state electrolyte film, and a diaphragm-free all-solid-state battery. Background Art

[0002] At present, due to the use of liquid electrolytes and diaphragms in lithium-ion batteries, in high-energy-density energy storage devices, the flammable and explosive liquid organic electrolyte seriously affects the safety of lithium-ion batteries as the temperature rises, and the use of diaphragms inevitably affects the energy density of the battery. In order to improve the energy density and safety of lithium-ion batteries, solid electrolyte membranes are used in the prior art to replace diaphragms and liquid electrolytes.

[0003] In the prior art, patent application CN 109786819 A discloses an electrolyte composition and a polymer electrolyte membrane, a polymer electrolyte and a preparation method thereof, and an all-solid-state battery and a preparation method thereof, which can improve the battery's specific capacity and cycle life and other performance by optimizing the selection of polymers, lithium salts, ionic liquids and cross-linking agents. Patent application CN117038842 A discloses a pole piece with a multi-layer solid electrolyte and a preparation method, a solid-state battery and a preparation method thereof, which increases the interface contact between the solid electrolyte and the electrode active material, and between the solid electrolyte and the battery pole piece by making the solid-state battery pole piece contain a multi-layer electrolyte layer such as an interface modification layer and an organic polymer solid electrolyte layer, so as to achieve the replacement of the diaphragm, build a stable solid-state battery interface, and improve the cycle stability of the solid-state battery.

[0004] However, there is still room for further improvement in the electrochemical performance and high-temperature stability of current solid-state batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The present invention provides an electrolyte slurry and a preparation method and application thereof, so as to solve the above-mentioned defects in the prior art and further improve the electrochemical performance and high-temperature stability of solid-state batteries.

[0007] Based on this, the present invention has the following technical solutions: In the first aspect, the present invention first provides an electrolyte slurry, which is mainly prepared by blending and modifying a first polymer, an inorganic material, a second polymer and a lithium salt; the first polymer is a polysulfide compound, and the polysulfide compound includes one or more of a monosulfide polymer, a disulfide polymer and a polysulfide polymer.

[0008] The present invention first discovers and proposes that since the electronegativity of sulfur ions is less than that of oxygen ions, sulfur has stronger polarizability, and the sulfur in the chain segment can not only form a coordination compound with the lithium salt, but also the content of S groups on the polysulfide main chain is much higher than the content of O groups on the traditional ether polymer main chain, providing more coordination sites, so the polysulfide has higher ionic conductivity; due to the abundant dynamic covalent bonds in the polysulfide, namely disulfide bonds, the polysulfide can maintain the stability of the covalent bonds while having a certain dynamic reversibility, and has high thermal stability, high mechanical strength and self-healing properties. After the above-mentioned polysulfide compound solution is blended and modified with the inorganic material, the second polymer and the lithium salt, the polysulfide is a small molecule polymer, which can be used as a plasticizer and a second phase polymer to reduce the crystallinity of the solid electrolyte membrane, improve the ionic conductivity and the ion migration number, and the polysulfide has better compatibility with the inorganic material, which is more conducive to improving the ionic conductivity, thereby further improving the electrochemical performance of the battery; at the same time, the present invention further finds that the introduction of the above-mentioned polysulfide compound can form a dense lithium sulfide SEI on the lithium metal negative electrode, inhibit the formation of lithium dendrites and eliminate the dead lithium generated during the cycle, thereby improving the cycle stability.

[0009] Preferably, the monomers of the monosulfide polymer include , , or ; The monomers of the disulfide polymer include , or ; The monomers of the polysulfide polymer include ; Among them, R1, R2, R3, R4, R5, R8, R9, R 10 and R 11 The same or different represent substituted or unsubstituted C1~C5 alkyl, substituted or unsubstituted C1~C5 monocarboxylic acid, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C6~C 30 R6 and R7 are the same or different and represent substituted or unsubstituted C1-C5 alkylene, substituted or unsubstituted C6-C8 alkylene, substituted or unsubstituted C1-C5 alkylene, substituted or unsubstituted C2-C8 ... 30 Arylene, substituted or unsubstituted C6~C 30 The invention also comprises a fused ring arylene group, a substituted or unsubstituted C2-C8 heteroarylene group, a substituted or unsubstituted amine group, a substituted or unsubstituted hydrazine group, a substituted or unsubstituted ester group, a sulfone group or a sulfoxide group, or a group consisting of the above groups.

[0010] Preferably, R1, R2, R3, R4, R5, R8, R9, R 10 and R 11 represents, identically or differently, a substituted or unsubstituted alkyl group, a substituted or unsubstituted phenyl or naphthyl group, a substituted or unsubstituted five-membered or six-membered monocyclic or bicyclic heteroaryl group, a substituted or unsubstituted carboxyl group, a substituted or unsubstituted amine group, a substituted or unsubstituted hydrazine group, a substituted or unsubstituted ester group, a sulfone group or a sulfoxide group, wherein the heteroatom in the five-membered or six-membered monocyclic or bicyclic heteroaryl group includes at least one of oxygen, sulfur and nitrogen; when substituted, the substituent includes an alkyl group, a carboxyl group, a hydroxyl group, a nitro group, a cyano group, an amine group, an acyl group or an azido group.

[0011] Preferably, R6 and R7, identically or differently, represent substituted or unsubstituted alkylene, substituted or unsubstituted phenylene or naphthylene; substituted or unsubstituted five-membered or six-membered monocyclic or bicyclic heteroaryl, substituted or unsubstituted carboxyl, substituted or unsubstituted amine, substituted or unsubstituted hydrazine, substituted or unsubstituted ester, sulfone or sulfoxide, wherein the heteroatoms in the five-membered or six-membered monocyclic or bicyclic heteroaryl include at least one of oxygen, sulfur and nitrogen; when substituted, the substituent includes alkyl, carboxyl, hydroxyl, nitro, cyano, amine, acyl or azido.

[0012] In the present invention, the term "substituted or unsubstituted alkyl" refers to an unsubstituted alkyl; or, one or more hydrogen atoms in the alkyl are substituted. The term "substituted or unsubstituted phenyl or naphthyl" refers to an unsubstituted phenyl or naphthyl; or, one or more hydrogen atoms on the benzene ring or naphthalene ring are substituted. The term "substituted or unsubstituted five-membered or six-membered monocyclic or bicyclic heteroaryl" refers to an unsubstituted five-membered or six-membered monocyclic or bicyclic heteroaryl, or, one or more hydrogen atoms on the heteroaryl ring are substituted. The term "substituted or unsubstituted carboxyl" refers to an unsubstituted carboxyl, or, the hydrogen atom connected to the carbon in the carboxylic acid is substituted. The term "substituted or unsubstituted amino" refers to an unsubstituted amino, or, one or more hydrogen atoms in the amino are substituted. The term "substituted or unsubstituted hydrazine" refers to an unsubstituted hydrazine, or, one or more hydrogen atoms in the hydrazine are substituted. The term "substituted or unsubstituted ester" refers to an unsubstituted ester, or, the atom connected to the carbon in the ester is substituted. The term "substituted or unsubstituted alkylene" refers to an unsubstituted alkylene; or, one or more hydrogen atoms in the alkylene are substituted. The term "substituted or unsubstituted phenylene or naphthylene" refers to an unsubstituted phenylene or naphthylene; or, one or more hydrogen atoms on the phenylene ring or naphthylene ring are substituted. The term "substituted or unsubstituted five-membered or six-membered monocyclic or bicyclic heteroarylene" refers to an unsubstituted five-membered or six-membered monocyclic or bicyclic heteroarylene; or, one or more hydrogen atoms on the heteroarylene ring are substituted.

[0013] When substituted, the substituents are preferably one or more groups independently selected from alkyl, carboxyl, hydroxy, nitro, cyano, amine, acyl, or azido groups, and the like.

[0014] More preferably, R1, R2, R3, R4, R5, R8, R9, R 10 and R 11 represents, identically or differently, nitrocarboxyphenyl, carboxyphenyl, aminophenyl, aminonaphthyl, azidophenyl, methylphenyl; carboxyethyl, carboxypropyl, carboxybutyl or glycolic acid; morpholinyl, thiazolyl, thienyl or thianthrenyl, propionohydrazide, diethylamino, dimethyl propionate, sulfone or sulfoxide.

[0015] More preferably, R6 and R7, identically or differently, represent substituted or unsubstituted nitrocarboxyphenylene, carboxyphenylene, aminophenylene, aminonaphthylene, azidophenylene, methylphenylene, morpholine-diyl, thiazole-diyl, thiophene-diyl or thianthrene-diyl, propionohydrazide, diethylamino, dimethyl propionate, sulfone or sulfoxide.

[0016] More preferably, R1, R2, R3, R4, R5, R8, R9, R 10 and R 11 R6 and R7, which are the same or different, represent methylphenyl, nitrocarboxyphenyl, phenylamino, carboxyethyl, sulfone or dimethyl propionate. R6 and R7, which are the same or different, represent tolylene, nitrocarboxyphenylene, aminophenylene or sulfone.

[0017] Preferably, the molecular weight of the polysulfide compound is 2000-6000.

[0018] The present invention finds that by controlling the molecular weight of the polysulfide compound to be within the above range, it is possible to avoid high crystallinity of large molecular weight polysulfide, which is not conducive to ion transport; when the molecular weight is lower than the above range, the dynamic disulfide bond content in the polymer is low, and the mechanical strength and thermal stability are poor.

[0019] Preferably, the inorganic material includes an inorganic solid electrolyte and / or an inorganic ceramic; the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a borate solid electrolyte and a nitride solid electrolyte.

[0020] In the present invention, the oxide solid electrolyte includes one or more of a perovskite-type oxide solid electrolyte, a garnet-type oxide solid electrolyte, and a NASICON-type oxide solid electrolyte.

[0021] In the present invention, the sulfide solid electrolyte may be one or more of lithium germanium phosphorus sulfur, lithium silicon phosphorus sulfur chlorine, lithium phosphorus sulfur bromine, lithium phosphorus sulfur iodine, lithium phosphorus sulfur chlorine, lithium thiophosphate, and vitreous sulfide; the halide solid electrolyte may be Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1), Li2XCl4 (X is selected from Cd or Mg), Li2X'I4 (X is selected from Cd or Zn), LiMCl5X''' (M is selected from one or more of La, Ta, Nb, and X''' is selected from O, Cl, F, or OH), Li 3-y Zr y M’ 1- y Cl6 (M’ is selected from one or more of Y, Er, Yb, Ho, Lu, and 0 < y < 1); the borate solid electrolyte may be one or more of Li2B4O7, Li2O - B2O3 - P2O5; the nitride solid electrolyte may be one or more of LiPON, Li3N, Li7PN4, LiSi2N3.

[0022] More preferably, when the inorganic solid electrolyte is an oxide solid electrolyte, the oxide solid electrolyte has a high ionic conductivity and an electrochemical window. At room temperature, the ionic conductivity can be greater than 10 -3 S / cm, and the electrochemical stability window can also be greater than 5V; during the preparation of the solid electrolyte membrane, the oxide has extremely high compatibility and stability with polysulfide compounds, lithium salts, and solvents, and no side reactions will occur to cause performance degradation; the oxide has a decomposition temperature greater than 1000°C and advantages such as being incombustible and non - supporting combustion, which can improve the thermal stability of the solid electrolyte membrane at high temperatures and the safety of the battery cell at high temperatures.

[0023] Further preferably, the oxide solid electrolyte includes one or more of perovskite - type oxide solid electrolytes, garnet - type oxide solid electrolytes, and NASICON - type oxide solid electrolytes; the perovskite - type oxide solid electrolyte is selected from lithium lanthanum titanium oxide; the garnet - type oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, niobium - doped lithium lanthanum zirconium oxide, tantalum - doped lithium lanthanum zirconium oxide, and niobium - tantalum co - doped lithium lanthanum zirconium oxide; the NASICON - type oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium yttrium titanium phosphate, and lithium germanium aluminum phosphate.

[0024] Preferably, the inorganic ceramic includes one or more of nitrides, carbides, metal oxides and non-metal oxides; more preferably, the nitride is selected from one or more of silicon nitride, titanium nitride, aluminum nitride, boron nitride and magnesium nitride; the carbide is selected from one or more of silicon carbide and boron carbide; the metal oxide is selected from one or more of aluminum oxide, titanium dioxide, zirconium dioxide and magnesium oxide; the non-metal oxide is selected from one or more of silicon dioxide and boron oxide.

[0025] Preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalatoborate.

[0026] Preferably, the second polymer includes one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-chlorotrifluoroethylene, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polypropylene carbonate, polyphenylene sulfide, polyethyl cyanoacrylate, polypentylene succinate, polyvinyl chloride, polyacrylic acid, polyvinyl carbonate, polyvinyl butyral, polyvinyl pyrrolidone, polyimide, polyacrylate, polyurethane, nitrile rubber, styrene-butadiene rubber and carboxymethyl cellulose.

[0027] In a second aspect, the present invention provides a method for preparing the electrolyte slurry, comprising the following steps: S1: dissolving the monomer of the polysulfide compound and the initiator in a solvent, and polymerizing to obtain the first polymer solution; S2: mixing the first polymer solution, the inorganic material, the second polymer and the lithium salt to obtain the electrolyte slurry.

[0028] In the present invention, those skilled in the art can polymerize the monomers of the polysulfide compound according to the existing polymerization method disclosed in the prior art to obtain the first polymer.

[0029] In the specific implementation process, the polymerization method in S1 can be any process method in the prior art such as oxidation method, photoinitiation method or thermal initiation method.

[0030] As some embodiments of the present invention, when the polymerization is carried out by oxidation, the oxidation initiator can be one or more of dimethyl sulfoxide, iodine and hydrogen peroxide.

[0031] As some embodiments of the present invention, when photoinitiation is used for polymerization, the photoinitiator can be one or more of 2-hydroxy-2-methylpropiophenone, ethyl (2,4,6-trimethylbenzoyl)phosphonate, ethyl 4-dimethylaminobenzoate, 1-hydroxycyclohexyl phenyl ketone, benzoin dimethyl ether, methyl o-benzoylbenzoate and 4-chlorobenzophenone.

[0032] As some embodiments of the present invention, when the polymerization is carried out by thermal initiation, the thermal initiator can be one or more of 2,2'-azobis(isobutyronitrile) (AIBN), benzoyl peroxide (BPO), azobisisoheptanenitrile (ABVN), diethylhexyl peroxydicarbonate (EHP), dimethyl azobisisobutyrate, dibenzoyl oxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, mercaptobenzene, thiolates and alkyl mercaptans.

[0033] Preferably, the solvent comprises one or more of tetrahydrofuran, DMF, anisole, xylene and acetone.

[0034] Preferably, in S1, the polymerization temperature is 70-120°C.

[0035] The present invention finds that in the prior art, when polymerizing the monomers of the above-mentioned polysulfide compounds, the general polymerization temperature is 130~200°C, that is, at least above 130°C; but the present invention finds that a polymerization temperature above 130°C will lead to poor uniformity of the system, which is not conducive to controlling the viscosity of the electrolyte slurry.

[0036] In a second aspect, the present invention provides a pole piece, including a positive pole piece or a negative pole piece, on which the electrolyte slurry is coated.

[0037] In a third aspect, the present invention provides a method for preparing the above-mentioned electrode sheet, comprising: coating, casting and spraying the electrolyte slurry onto a positive electrode sheet or a negative electrode sheet.

[0038] In a fourth aspect, the present invention provides a separator, wherein a base film of the separator is coated with the electrolyte slurry.

[0039] Preferably, the base film includes polyethylene terephthalate (PET), ethylene terephthalate, polybutylene terephthalate, polyethylene (PE), polypropylene (PP), poly-1-butene, polyisobutylene, polybutadiene, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, cellulose, polyvinyl alcohol, polymethyl methacrylate, polyurethane, polycarbonate, polysulfate, aluminum oxide film, polyimide non-woven film, polyaryl sulfone non-woven film, silicone oil release film, non-silicone release film, fluorine release film or glass fiber.

[0040] Preferably, the base film has a thickness of 1 to 50 μm, more preferably 2 to 20 μm.

[0041] In a fifth aspect, the present invention provides a method for preparing the above-mentioned separator, which comprises: coating the electrolyte slurry onto the base film.

[0042] In a sixth aspect, the present invention provides a solid electrolyte film, which is prepared from the electrolyte slurry.

[0043] In a seventh aspect, the present invention provides a method for preparing a solid electrolyte film, comprising: scraping the electrolyte slurry onto a glass plate to form the solid electrolyte film.

[0044] In an eighth aspect, the present invention provides a membrane-free all-solid-state battery, which contains the above-mentioned electrode, membrane or solid electrolyte film.

[0045] The electrolyte slurry and the preparation method and application thereof provided by the present invention can further improve the electrochemical performance and high-temperature stability of the solid-state battery by introducing the polysulfide compound into the raw material system. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0048] Example 1

[0049] This embodiment provides an electrolyte slurry, which includes the following components in parts by weight: 15 parts of a monomer of a monosulfide polymer; the monomer of the monosulfide polymer is , the molecular weight after polymerization is 4200; 65 LLZTOs; 5 parts PVDF-HFP; 15 parts of LiTFSI; 150 parts THF.

[0050] In this embodiment, PVDF-HFP is a polyvinylidene fluoride-hexafluoropropylene copolymer, which is commercially available, with a brand model of arkema LBG and a molecular weight of 700,000 to 800,000.

[0051] This embodiment also provides a method for preparing an electrolyte slurry, comprising the following steps: S1: 15 portions and 1 part of mercaptobenzene were dissolved in 150 parts of THF, and heated at 120°C for polymerization for 6 hours to obtain a monosulfide polymer solution; S2: 65 parts of LLZTO, 5 parts of PVDF-HFP, and 15 parts of LiTFSI were added to the above monosulfide polymer solution and mixed to obtain an electrolyte slurry.

[0052] This embodiment also provides a method for preparing a solid electrolyte membrane, comprising: coating the above electrolyte slurry on PET, and baking at 80° C. for 2 hours to obtain a solid electrolyte membrane.

[0053] This embodiment further provides a composite electrode, which adopts the following electrode composite technology, and its preparation method includes the following steps: S1: Disperse polyvinylidene fluoride (PVDF), conductive carbon black (SP) and NCM-811 in NMP in sequence to prepare a positive electrode slurry, with a mass ratio of 2:2:96.

[0054] S2: Coat the positive electrode slurry on the aluminum foil, bake and roll to obtain the positive electrode sheet, with a positive electrode surface density of 25 mg / cm 2 .

[0055] S3: coating the electrolyte slurry on the positive electrode plate, and baking at 80° C. for 2 h to obtain a composite electrode plate.

[0056] Example 2

[0057] This embodiment provides an electrolyte slurry, which is different from the embodiment 1 only in that: Replace with an equal amount , polymerization gave a monosulfide polymer with a molecular weight of 4700.

[0058] Example 3

[0059] This embodiment provides an electrolyte slurry, which is different from the embodiment 1 only in that: Replace with an equal amount , polymerization gave a disulfide polymer; its molecular weight was 3900.

[0060] Example 4

[0061] This embodiment provides an electrolyte slurry, which is different from the embodiment 1 only in that: Replace with an equal amount , polymerization gave a disulfide polymer; its molecular weight was 5500.

[0062] Example 5

[0063] This embodiment provides an electrolyte slurry, which is different from the embodiment 1 only in that: Replace with , polymerization gave a disulfide polymer with a molecular weight of 5100.

[0064] Example 6

[0065] This embodiment provides an electrolyte slurry, which is different from the embodiment 1 only in that: Replace with equal amount , polymerization gave a trisulfide polymer with a molecular weight of 4700.

[0066] Example 7

[0067] This embodiment provides an electrolyte slurry, which is different from the embodiment 1 only in that: Replaced with an equal amount of thiomalic acid , polymerization gave a monosulfide polymer with a molecular weight of 4300.

[0068] Example 8

[0069] This embodiment provides an electrolyte slurry, which is different from Embodiment 1 in that the molecular weight of the monosulfide polymer obtained by polymerization is 8400.

[0070] Comparative Example 1

[0071] This comparative example provides an electrolyte slurry, which is different from Example 1 only in that: Replace with an equal amount of cage-type silsesquioxane.

[0072] Comparative Example 2

[0073] This comparative example provides an electrolyte slurry, which differs from Example 1 only in that the polysulfide compound in the electrolyte slurry is removed, and the reduced amount is replaced by the inorganic material, the second polymer, the lithium salt and the organic solvent in Example 1 in proportion.

[0074] Test Example 1

[0075] 1. The electrochemical performance and high temperature stability of the electrode sheets prepared in the embodiment and the comparative example were tested. The results are shown in Table 1.

[0076] Test methods include: Ion conductivity test: Assemble a stainless steel symmetrical battery and test the AC impedance of the battery. Ion conductivity = electrolyte membrane thickness / (impedance*area).

[0077] Electrochemical window test: Assemble a stainless steel-electrolyte membrane-lithium metal battery and use linear sweep voltammetry test. The voltage when the decomposition current is greater than 100 uA cm-2 is defined as the electrochemical window.

[0078] Lithium symmetric battery cycling: Assembled lithium metal symmetric cells and cycled at 0.5 mA / cm 2 The current is constant current charged and discharged, and the time when the corresponding battery short circuit occurs is recorded.

[0079] Capacity retention rate test: Assemble the composite electrode-lithium metal battery, perform constant current charge and discharge test at 0.33C current, and monitor the corresponding capacity retention rate after 200 cycles.

[0080] Thermal shrinkage test: The electrolyte membrane was cut into 5cm*5cm squares and placed in a 150℃ oven for 1h. Thermal shrinkage = (original electrolyte membrane length - electrolyte membrane length after baking) / original electrolyte membrane length.

[0081] Table 1

[0082] 2. The performance of the solid electrolyte films prepared in the examples and comparative examples was tested. The results are shown in Table 2.

[0083] Test methods include: Tensile strength test: The solid electrolyte membrane was cut into strips of 10 cm × 3 cm and the tensile strength was tested using a tensile testing machine at a tensile rate of 20 mm / min.

[0084] Self-healing performance test: The solid electrolyte membrane was cut into two 5 cm × 5 cm square strips, and the two solid electrolyte membranes were placed in contact for 1 hour to observe whether they could self-heal into a long strip.

[0085] Table 2

[0086] It should be noted that experimental results show that when the polymerization temperature is greater than 120°C, such as the conventionally used 170°C, the system uniformity during the reaction is poor, which is not conducive to controlling the viscosity of the electrolyte slurry, thereby affecting the performance of the electrode and the solid electrolyte membrane.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrolyte slurry, characterized in that: It is prepared by blending and modifying a first polymer, an inorganic material, a second polymer and a lithium salt; the first polymer is a polysulfide compound, and the polysulfide compound includes one or more of a monosulfide polymer, a disulfide polymer and a polysulfide polymer.

2. The electrolyte slurry according to claim 1, characterized in that The monomers of the monosulfide polymer include , , or ; The monomers of the disulfide polymer include , or ; The monomers of the polysulfide polymer include ; Among them, R1, R2, R3, R4, R5, R8, R9, R 10 and R 11 The same or different represent substituted or unsubstituted C1~C5 alkyl, substituted or unsubstituted C1~C5 monocarboxylic acid, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C6~C 30 R6 and R7 are the same or different and represent substituted or unsubstituted C1-C5 alkylene, substituted or unsubstituted C6-C8 alkylene, substituted or unsubstituted C1-C5 alkylene, substituted or unsubstituted C2-C8 ... 30 Arylene, substituted or unsubstituted C6~C 30 The invention also comprises a fused ring arylene group, a substituted or unsubstituted C2-C8 heteroarylene group, a substituted or unsubstituted amine group, a substituted or unsubstituted hydrazine group, a substituted or unsubstituted ester group, a sulfone group or a sulfoxide group, or a group consisting of the above groups.

3. The electrolyte slurry according to claim 2, characterized in that R1, R2, R3, R4, R5, R8, R9, R 10 and R 11 represents identically or differently a substituted or unsubstituted alkyl, a substituted or unsubstituted phenyl or naphthyl, a substituted or unsubstituted five-membered or six-membered monocyclic or bicyclic heteroaryl, a substituted or unsubstituted carboxyl, a substituted or unsubstituted amine, a substituted or unsubstituted hydrazine, a substituted or unsubstituted ester, a sulfone or a sulfoxide, wherein the heteroatom in the five-membered or six-membered monocyclic or bicyclic heteroaryl includes at least one of oxygen, sulfur and nitrogen; when substituted, the substituent includes an alkyl, carboxyl, hydroxyl, nitro, cyano, amine, acyl or azido group; R6 and R7, identically or differently, represent substituted or unsubstituted alkylene, substituted or unsubstituted phenylene or naphthylene; substituted or unsubstituted five-membered or six-membered monocyclic or bicyclic heteroarylene, substituted or unsubstituted carboxyl, substituted or unsubstituted amine, substituted or unsubstituted hydrazine, substituted or unsubstituted ester, sulfone or sulfoxide, wherein the heteroatom in the five-membered or six-membered monocyclic or bicyclic heteroaryl includes at least one of oxygen, sulfur and nitrogen; when substituted, the substituent includes alkyl, carboxyl, hydroxyl, nitro, cyano, amine, acyl or azido.

4. The electrolyte slurry according to any one of claims 1 to 3, characterized in that The molecular weight of the polysulfide compound is 2000-6000.

5. The electrolyte slurry according to any one of claims 1 to 3, characterized in that: The inorganic material includes an inorganic solid electrolyte and / or an inorganic ceramic; the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a borate solid electrolyte and a nitride solid electrolyte; Preferably, the inorganic solid electrolyte is an oxide solid electrolyte; the oxide solid electrolyte includes one or more of a perovskite oxide solid electrolyte, a garnet oxide solid electrolyte, and a NASICON oxide solid electrolyte; More preferably, the perovskite-type oxide solid electrolyte is selected from lithium lanthanum titanium oxide; the garnet-type oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, niobium-doped lithium lanthanum zirconium oxide, tantalum-doped lithium lanthanum zirconium oxide and niobium-tantalum dual-doped lithium lanthanum zirconium oxide; the NASICON-type oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium yttrium titanium phosphate and lithium aluminum germanium phosphate; and / or, the inorganic ceramic comprises one or more of nitrides, carbides, metal oxides and non-metal oxides; Preferably, the nitride is selected from one or more of silicon nitride, titanium nitride, aluminum nitride, boron nitride, and magnesium nitride; the carbide is selected from one or more of silicon carbide and boron carbide; the metal oxide is selected from one or more of aluminum oxide, titanium dioxide, zirconium dioxide, and magnesium oxide; the non-metallic oxide is selected from one or more of silicon dioxide and boron oxide; and / or, the lithium salt comprises one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate; And / or, the second polymer includes one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-chlorotrifluoroethylene, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polypropylene carbonate, polyphenylene sulfide, polyethyl cyanoacrylate, polypentylene succinate, polyvinyl chloride, polyacrylic acid, polyvinyl carbonate, polyvinyl butyral, polyvinyl pyrrolidone, polyimide, polyacrylate, polyurethane, nitrile rubber, styrene-butadiene rubber and carboxymethyl cellulose.

6. The method for preparing the electrolyte slurry according to any one of claims 1 to 5, characterized in that: The steps include: S1: dissolving the monomer of the polysulfide compound and the initiator in a solvent for polymerization to obtain the first polymer solution; preferably, the polymerization temperature is 70-120° C.; S2: mixing the first polymer solution, the inorganic material, the second polymer and the lithium salt to obtain the electrolyte slurry.

7. A pole piece, including a positive pole piece or a negative pole piece, characterized in that: The electrode sheet is covered with the electrolyte slurry according to any one of claims 1 to 6 or the electrolyte slurry prepared by the preparation method according to claim 6.

8. A diaphragm, characterized in that: The base film of the separator is coated with the electrolyte slurry according to any one of claims 1 to 6; Preferably, the base film comprises polyethylene terephthalate, ethylene terephthalate, polybutylene terephthalate, polyethylene, polypropylene, poly-1-butene, polyisobutylene, polybutadiene, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, cellulose, polyvinyl alcohol, polymethyl methacrylate, polyurethane, polycarbonate, polysulfate, aluminum oxide film, polyimide nonwoven film, polyaryl sulfone nonwoven film, silicone oil release film, non-silicone release film, fluorine release film or glass fiber; Preferably, the base film has a thickness of 1 to 50 μm, more preferably 2 to 20 μm.

9. A solid electrolyte film, characterized in that: The electrolyte slurry is prepared from the electrolyte slurry according to any one of claims 1 to 6.

10. A diaphragm-free all-solid-state battery, characterized in that: Contains the pole piece according to claim 7, the diaphragm according to claim 8 or the solid electrolyte film according to claim 9.

Citation Information

Patent Citations

  • Electrolyte composition, polymer electrolyte membrane, polymer electrolyte and preparation method thereof, all-solid-state battery and preparation method thereof

    CN109786819A

  • Pole piece with multiple layers of solid electrolyte, preparation method of pole piece, solid-state battery and preparation method of solid-state battery

    CN117038842A

Cited By

  • Directional nanofiber-coated cubic phase garnet type LLZO composite solid electrolyte with three-dimensional structure and preparation method thereof

    CN120749218A